Kounis syndrome: A review article on epidemiology, diagnostic findings, management and complications of allergic acute coronary syndrome. (1st April 2017) - Abdelghany, Mahmoud; Subedi, Rogin; Shah, Siddharth; Kozman, Hani
Abstract: Kounis syndrome (KS) is a hypersensitivity coronary disorder induced by exposure to drugs, food, environmental and other triggers. Vasospastic allergic angina, allergic myocardial infarction (MI) and stent thrombosis with occluding thrombus infiltrated by eosinophils and/or mast cells constitute the three main variants of this syndrome. We reviewed 175 patients who fulfilled the definition of one of the three types of KS. The epidemiology, diagnostic findings, management and complications were reviewed in this article. Highlights: Kounis syndrome (KS) is allergic acute coronary syndrome, more common in middle aged men. There are 3 variants of KS. Type I, allergic coronary vasospasm, is the most common. The most common presentation of KS is ST elevation myocardial infarction. Management of KS targets cardiac revascularization and allergy treatment. KS has a relatively good prognosis with infrequent life threatening complications.